Transanal small bowel evisceration in a 3-year-old victim of motor vehicle accident - Minakshi Bhosale; Ameya Sangle; Ganesh Bhat; Praveen Dambal (Wolters Kluwer Medknow Publications, 2021)
Although motor vehicle accidents (MVAs) in children are common, pediatric rectal perforations secondary to MVAs leading to transanal evisceration of the small bowel are very rare. Herniation of bowel through breach in the rectal wall seen eviscerating through the anus is a surgical emergency requiring laparotomy and necessary surgical procedure. We report case of a 3-year-old boy, victim of run-over MVA accident, presenting with bilateral fracture shaft femur, fracture of the left humerus, and transanal small bowel evisceration. About 30-40 cm long, gangrenous, small bowel loop was hanging outside the anal canal. Two consecutive surgeries were performed to manage this unusual and complex case with an excellent outcome. This report is presented for an extremely rare presentation of MVA injury in a child.